Thermal radiation in subwavelength aluminum foam structures by finite-difference time-domain method. (June 2015) - Qiu, J.; Liu, L.H.; Hsu, P.-f.
Abstract: We investigated the thermal radiation properties of subwavelength aluminum foam structures in this work. A Maxwell׳s equation solution (Finite-Difference Time-Domain) method was used to numerically calculate spectral thermal radiation in subwavelength foam structures. Due to the complexity of the real foam structures, we started our researches by investigating two periodic structures (linear and staggered foam structures) with cubic representative elementary volume. Different number of layers from 1 to 5 has been studied. The cavity resonances that enhanced the absorption coefficient of the incident wave energy were clearly observed. The results also showed that the radiation properties of staggered foam structures can be affected by the polarization angle at normal incidence. Additionally, the absorption ratio of every layer of the foam structures has been studied. Finally, cavity resonance also can be clearly seen at oblique incidence. This work will provide an accurate validation result for the study of radiative transfer in subwavelength foam structures using the methods based on radiative transfer equation or geometrical optics in future. Highlights: FDTD method is used to study the thermal radiation of subwavelength foam structures. Thermal radiation properties of two different foam structures are compared. Cavity resonances are observed inside the cavities between neighboring layers. The spectral absorption ratio of every layer of foam structures is given.